Effect of streptozotocin-diabetes on rat liver mitochondrial adenosine triphosphatase turnover. - Jordá, A (1988)
The apparent turnover rates of some mitochondrial enzymes can be modified in diabetes. We studied the effect of streptozotocin-diabetes on the half-life of a protein tightly bound to the inner membrane, ATPase. The half-life (t 1/2), measured by the double-isotope technique, decreased by approx. 20% in diabetes (from approximately equal to 2.56 days in controls to approximately equal to 2.06 days in diabetic rats). These results suggest that diabetes produces an increase in degradation of ATPase by a mechanism which is not yet clear, possibly influenced by alterations induced by diabetes in hepatic lysosomes that are associated with hepatic autophagy.